Sukcesja osadowa kopalnego koryta rzeki meandrującej na przykładzie Radacznicy (woj. Wielkopolskie, Polska) = Sedimentary succession of a fossil meandering river channel on the example of Radacznica (Wielkopolska voivodeship, Poland) - Krupa, Adam; Hojan, Marcin; Rurek, Mirosław; Giętkowski, Tomasz (Journal of Education, Health and Sport, 2015)
Krupa Adam, Hojan Marcin, Rurek Mirosław, Giętkowski Tomasz. Sukcesja osadowa kopalnego koryta rzeki meandrującej na przykładzie Radacznicy (woj. Wielkopolskie, Polska) = Sedimentary succession of a fossil meandering river channel on the example of Radacznica (Wielkopolska voivodeship, Poland). Journal of Education, Health and Sport. 2015;5(5):263-274. ISSN 2391-8306. DOI 10.5281/zenodo.17735 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A263-274 https://pbn.nauka.gov.pl/works/560514 http://dx.doi.org/10.5281/zenodo.17735 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.04.2015. Accepted: 08.05.2015. Sukcesja osadowa kopalnego koryta rzeki meandrującej na przykładzie Radacznicy (woj. Wielkopolskie, Polska) Sedimentary succession of a fossil meandering river channel on the example of Radacznica (Wielkopolska voivodeship, Poland) Krupa Adam, Hojan Marcin, Rurek Mirosław, Giętkowski Tomasz Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Polska Abstrakt W niniejszym artykule przedstawiono wyniki badań prowadzonych w dolinie Radacznicy. Stanowi ona głęboko wciętą w wysoczyznę formę, która posiada miejscami płaskie dno. W jednej z wykonanych odkrywek stwierdzono występowanie specyficznej sedymentacji, która wskazuje na meandrujący charakter rzeki. Paleokoryta zostały szczegółowo przeanalizowane (typy osadów, rozmiary, rekonstrukcja środowiska), aby określić sukcesję osadową. Wyniki wskazują, że nawet tak małe rzeki jak Radacznica mogą zmieniać położenie swojego koryta w wyniku różnych czynników naturalnych, a w ostatnich latach również antropogenicznych. Słowa kluczowe: paleokoryta, sedymentacja, osady korytowe i pozakorytowe, dolina erozyjna. Abstract This paper presents results of research conducted in the Radacznica valley. The valley is deeply cut into the morainic upland and forms a rather narrow V-shaped gorge in its upper part as well as a wider, flat-bottomed section in its lower reaches. In one of the examined pits the evidences for the meandering nature of the river have been found. The structures of the paleochannel were analyzed in details to determine the sedimentary succession. The results show that even such small rivers as Radacznica can change the position of its bed due to the influences of natural factors as well as in recent years the anthropogenic. Key words: paleochanels, sedmientation, chanel and overbank deposits, erosion valley.